Energy audit in Block 3 in S & T tower towards energy efficiency in UiTM Shah Alam: article / Muhammad Azwan Abdul Aziz - Abdul Aziz, Muhammad Azwan (2013)
The main purpose of this project is to study on the energy consumption and to give recommendation to reduce the energy wastage in the building in Block 3 S&T Tower. The energy consumption was recorded using Fluke Meter 1750. The meter was installed at the Sub-Switch Board (SSB) at Block 3 for two different operations namely during normal working days and during semester break. Based on the data collected, the pattern of energy usage was analyzed and energy wastage was identified strategic steps are recommended to reduce total energy consumption at Block 3.